2011
DOI: 10.1002/jnr.22651
|View full text |Cite
|
Sign up to set email alerts
|

Topographic mapping of retinal neurons in the european anchovy by nuclear staining and immunohistochemistry

Abstract: The anchovy retina is unique among vertebrates in being designed for polarization-contrast vision and has a marked cone area in the ventrotemporal quadrant for acute vision in the frontal field of view. Whereas cone topography and fine structure have been well examined in the European anchovy, the morphological organization of its inner retina is poorly understood so far. Using fluorescence staining of cell nuclei in combination with antibody stainings, the 3D pattern of cell nuclei was recorded coevally in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
(85 reference statements)
2
6
1
Order By: Relevance
“…This results in at least a three‐fold increase in the cell density and, according to our estimation, an almost twofold increase in spatial resolution. That agrees with the calculated cone ratios for the ventro‐temporal and central retina in northern and European anchovies (1: 3.5 and 1: 4, respectively) (O'Connell, ; Heß, ; Koch and Heß, ). The detectable distance of a 1 mm diameter prey estimated using the formula provided by Miyazaki and Kobayashi () is approximately 12–25 cm for the Japanese anchovy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This results in at least a three‐fold increase in the cell density and, according to our estimation, an almost twofold increase in spatial resolution. That agrees with the calculated cone ratios for the ventro‐temporal and central retina in northern and European anchovies (1: 3.5 and 1: 4, respectively) (O'Connell, ; Heß, ; Koch and Heß, ). The detectable distance of a 1 mm diameter prey estimated using the formula provided by Miyazaki and Kobayashi () is approximately 12–25 cm for the Japanese anchovy.…”
Section: Discussionsupporting
confidence: 87%
“…Small pieces were excised from certain regions of the same retina and subjected to morphological and microspectrophotometric investigations. The locations from which the material was resected corresponded to the retinal map of the Japanese anchovy (Miyazaki and Kobayashi, ) that is similar to retinal maps of other species of the same genus Engraulis (Heß et al, ; Koch and Heß, ; Novales Flamarique, ).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…We should note that the cell densities reported in this study for anchovy and sardine are much lower than in previous studies (O'Connell, ; Koch et al, ; Koch and Heβ, ). In the two papers by Koch et al () on E. encrasicolu s and by O'Connell () on E. mordax and S. caerulea , the ganglion cell density is about five times higher than in this study.…”
Section: Discussioncontrasting
confidence: 78%
“…In these three species, the topographical maps of the ganglion cell showed that the highest density area was localized at the ventrotemporal quadrant of the retina, that is, temporal of the optic cleft, and their visual “interest” was hypothesized to be directed frontally upward. Also in the European anchovy ( E. encrasicolus ), the highest ganglion cell density area was observed in the ventrotemporal quadrant, and a topographical resemblance was found between ganglion and cone cell distribution (Koch et al, ; Koch and Heβ, ). The density of cone cells across the retina was also measured in other anchovies and sardines ( S. caeruleus , Alosa sapidissima , E. mordax , and Anchoa compressa , O'Connell, ; Cetengraulis mysticetus and Anchovia macrolepidota , Heß, ), and all topographical maps showed a sharply defined area of high cone cell density in the ventrotemporal quadrant.…”
Section: Discussionmentioning
confidence: 99%